Evaluation of six minute walking test in patients with single chamber rate responsive pacemakers. Issue 2 (August 1994) - Provenier, F; Jordaens, L
Abstract : OBJECTIVE--To validate a simplified exercise protocol (the six minute walk) as a means of evaluating pacing modes and rate responsive pacemakers. DESIGN--Two groups of patients with different pacemaker types (activity and dual sensor) were randomly assigned to four consecutive pacing settings (fixed rate--or VVI at 60, 85, and 110/min, and optimal rate response--or VVIR). A third group of elderly patients without arrhythmias or conduction disturbances formed a control population. SETTING--Ambulatory consultation for patients with a pacemaker in a tertiary referral centre for treatment of arrhythmias. SUBJECTS--16 patients with rate responsive pacemakers for complete heart block and limited functional capacity and 13 controls with normal chronotropic competence. INTERVENTIONS--Submaximal exercise protocol with 6 minutes walking and continuous recording of electrocardiogram. MAIN OUTCOME MEASURES--Achieved distance and scored degree of exertion during walking in the four settings in the patients with a pacemaker; differences in rate behaviour in VVIR mode between the two pacemaker types; comparison of the pacing rate with the heart rate of the control population. RESULTS--The six minute walk was performed better in VVIR than VVI 60. In VVI 85 the distance was also significantly longer than in VVI 60. The rise in pacing rate of activity pacemakers was steeper than that of the dual sensor pacemakers and differed from the heart rate in the controls at 90 seconds. CONCLUSIONS--The studied test protocol was able to show differences in exercise capacity between pacing modes. Different rate responses between the evaluated sensor types could be established. The six minute walking test gives enough information to program and reprogram single chamber rate responsive pacemakers.